2018
DOI: 10.1177/0886260518775753
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Intimate Partner Violence Before, During, and After Pregnancy in Bangladesh

Abstract: Intimate partner violence (IPV) against pregnant or postpartum women is known to have multiple detrimental effects on women and their children. Although results from past research suggest much continuity in trajectories of IPV, it is unclear whether pregnancy interrupts or augments these patterns. Little is known about how physical, sexual, and psychological IPV change and overlap throughout a woman's transition to parenthood. Relying on population-based data, this study examines the prevalence, co-occurring n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 88 publications
(140 reference statements)
3
25
0
Order By: Relevance
“…The current study is drawn from a much larger project, which mainly investigates maternal and child health before, during and after pregnancy in Bangladesh. This extensive dataset was used to produce several research outcomes exploring the correlates and changing pattern of intimate partner violence (IPV) before, during, and after pregnancy [ 39 , 40 ], the influence of IPV on experiencing PPD [ 41 ], maternal healthcare services [ 42 ] and suicidal ideation [ 8 ], psychosocial factors of EBF [ 11 ], and the influence of childhood maltreatment on EBF behaviours [ 43 ]. As described previously [ 11 , 41 ], a population-based cross-sectional survey of new mothers was carried out between October 2015 and January 2016 in two Upazilas (sub-districts) of the Chandpur district of Bangladesh.…”
Section: Methodsmentioning
confidence: 99%
“…The current study is drawn from a much larger project, which mainly investigates maternal and child health before, during and after pregnancy in Bangladesh. This extensive dataset was used to produce several research outcomes exploring the correlates and changing pattern of intimate partner violence (IPV) before, during, and after pregnancy [ 39 , 40 ], the influence of IPV on experiencing PPD [ 41 ], maternal healthcare services [ 42 ] and suicidal ideation [ 8 ], psychosocial factors of EBF [ 11 ], and the influence of childhood maltreatment on EBF behaviours [ 43 ]. As described previously [ 11 , 41 ], a population-based cross-sectional survey of new mothers was carried out between October 2015 and January 2016 in two Upazilas (sub-districts) of the Chandpur district of Bangladesh.…”
Section: Methodsmentioning
confidence: 99%
“…The impact of sequential and/or concurrent GBV may differ than that of single GBV exposures (Alexander, Amerigo, & Harrelson, 2018). The timing of exposure also may matter; for instance, the SRH effects of IPV before versus during pregnancy may differ (Islam, Broidy, Mazerolle, Baird, & Mazumder, 2018). To create interventions, a better understanding of polyvictimization against girls and women in LMICs will be essential (Grose et al, 2019;Le, Holton, Romero, & Fisher, 2018;Yount et al, 2017).…”
Section: Scope Of Gbv Exposuresmentioning
confidence: 99%
“…Though the government in Bangladesh has enacted the Domestic Violence Act 2010 to control violence against women, the rates of IPV are still high in the country [ 39 ]. It is reported that around two-thirds of ever-married women experienced IPV at least once during their lives [ 40 ], which is a serious public health concern for women, especially during their pregnancy [ 41 ]. A higher prevalence of IPV in Bangladesh might be the reason for the underutilization of maternal healthcare services.…”
Section: Discussionmentioning
confidence: 99%